A multi-isotope approach to evaluate the potential of great cormorant eggs for contaminant monitoring. (March 2022) - Jones, Douglas; Ovegård, Maria; Dahlgren, Henrik; Danielsson, Sara; Greger, Maria; Landberg, Tommy; Garbaras, Andrius; ML Karlson, Agnes
Highlights: Evaluating a new species for contaminant monitoring. Stable isotopes to deduce breeding strategy. Isotope methods and ecological knowledge improve mercury contaminant interpretation. Abstract: Contaminant monitoring in biota is important for determining environmental status and to detect or prioritize action on hazardous substances. Predators higher up a food chain are often used for monitoring of contaminants that bioaccumulate. However, it is not always possible to find higher predators that are both abundant and have a wide distribution for national or international contaminant monitoring. Great cormorants ( Phalocrocorax carbo ) are a widespread and increasingly common top predator of fish in fresh, brackish and salt water. We evaluate the suitability of great cormorant eggs as a matrix for contaminant monitoring by using stable isotopes of carbon, nitrogen and sulfur. Despite the fact that cormorants are migratory, egg isotope values showed a significant separation between five breeding colonies in Sweden (1 fresh water lake, 3 Baltic sites and 1 marine site). This high degree of separation indicates that eggs are primarily produced using local resources (not stored body resources) and that contaminants (mercury concentrations in this study) measured in eggs likely reflect levels in fish prey caught close to the breeding area. Compound specific stable isotope analysis was used to estimate cormorant trophic position (TP) and concentrations of mercury in eggs were positively related to TP. The results show that a multi-isotope approach, combined with good ecological diet knowledge allow for meaningful and comparative interpretation of mercury concentrations in biota and that great cormorant eggs appear a suitable matrix to measure locally derived and maternally transferred contaminants.